Rethinking the human resource (HR) strategy in the face of systematic failures in the devolved health sector in Kenya - Murimi, Michael; Lopar, Samuel; Kirande, Jairus; Kombo, Alice; Kipkorir, Bett (BOHR International Journal of Advances in Management Research, 2022)
This viewpoint paper is about rethinking the human resources (HR) strategy in the face of systematic failures in the devolved health sector in Kenya. The paper gives a background introduction of the health sector of Kenya as defined and established by the constitution of Kenya, explains the sharing of functions devolved in the health sector, and explains the history of devolution of the health sector. Under the identification and justification of the study, the paper highlights how specialized skills in health service provision are concentrated in urban centers and emphasizes a lack of inter-county transfer of services. The paper further explains the distribution of healthcare service provision, the current management of HR, and the statement of specific problems in Kenya; such problems include outcry from healthcare providers, which is manifested by frequent strikes across the country over issues to do with salaries, promotions, and career development. The viewpoint of the authors is that the seven building blocks of the health sector in Kenya are vital. The six building blocks can be handled by county governments while one block that deals with the management of HR of the health sector should be reformed, strengthened, and handled by the national government, hence the paper proposes the introduction of a health service commission to manage human resource components of the health sector. Finally, boost the Ministry of Health’s effective control of the healthcare workforce by advancing and integrating policies relating to health systems, services, and cross-sectorial collaboration to revive primary healthcare services and attain universal health coverage.